2018
DOI: 10.1016/j.yebeh.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol improves frequency and severity of seizures and reduces adverse events in an open-label add-on prospective study

Abstract: The objective of this study was to characterize the changes in adverse events, seizure severity, and frequency in response to a pharmaceutical formulation of highly purified cannabidiol (CBD; Epidiolex®) in a large, prospective, single-center, open-label study. We initiated CBD in 72 children and 60 adults with treatment-resistant epilepsy (TRE) at 5 mg/kg/day and titrated it up to a maximum dosage of 50 mg/kg/day. At each visit, we monitored treatment adverse events with the adverse events profile (AEP), seiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 24 publications
5
62
0
9
Order By: Relevance
“…As this is an ongoing study, numbers of patients receiving treatment for more than 12 months are too small to assess the long-term efficacy. Nevertheless, retention rates at 6 and 12 months are 78.1 and 73.1%, respectively, and comparable with other open label studies using plant-derived CBD (18). The role of clobazam-cannabidiol interaction in seizure reduction has been discussed before and is not fully understood (1).…”
Section: Discussionsupporting
confidence: 80%
“…As this is an ongoing study, numbers of patients receiving treatment for more than 12 months are too small to assess the long-term efficacy. Nevertheless, retention rates at 6 and 12 months are 78.1 and 73.1%, respectively, and comparable with other open label studies using plant-derived CBD (18). The role of clobazam-cannabidiol interaction in seizure reduction has been discussed before and is not fully understood (1).…”
Section: Discussionsupporting
confidence: 80%
“…CBD has been studied in recently conducted RCTs; however, the results are difficult to extrapolate to adults with epilepsy as these studies were conducted mainly in paediatric populations. In addition, these trials do not include hospitalized patients.…”
Section: Case Descriptionmentioning
confidence: 99%
“…On reviewing the published literature in detail, we found 3 previously published case reports over the last two decades, detailing 4 patient cases of adults using cannabis to reduce uncontrolled seizures . We also found 1 case series study, 7 RCTs, 1 observational study and 5 surveys examining the efficacy and safety of cannabis use in epilepsy. (Table S1) These studies showed a reduction or complete freedom from seizures following the use of CBD compared with placebo.…”
Section: Case Descriptionmentioning
confidence: 99%
“…11 Many other offlabel investigations into medical effectiveness of CBD have demonstrated effectiveness. [12][13][14] CBD, unlike its common cannabis-based cousin THC, does not elicit adverse physiological effects in up to 50 times recommended daily doses 15 and has even been shown to counteract intoxicating effects of THC. 16 Despite physiological effects being demonstrated through CBD usage, molecular mechanisms and the pharmacokinetic profile of CBD are much less understood than THC.…”
Section: Seizure Interventionmentioning
confidence: 99%